The total electric charge and time of application of galvanic currents to macrophages can optimize the release of IL-1β with low cell death - Alejandro Peñin-Franch; José Antonio García-Vidal; Ana Isabel Gómez; Pilar Escolar-Reina; Francesc Medina-Mirapeix; Pablo Pelegrín (Scientific Reports)
Abstract Galvanic current has been emerging as a novel therapy to regenerate chronic tissue lesions, including musculoskeletal and dermatological lesions. Recently, the NLRP3 inflammasome and IL-1β release have been identified as a signaling pathway triggered upon galvanic current application. However, the parameters for the clinical application of galvanic current remain subjective to the experience of the facultative in charge. In this study we used an in vitro model of macrophage culture and application of different combinations of the parameters of galvanic current to study IL-1β production and cell death. Increasing electric charge of galvanic current induces the release of IL-1β, but electric charges equal or higher to 144 mC also increase cell death. The release of IL-1β have a substantial variation within different electric charge of galvanic currents, being increased by decreasing the current and increasing the time of current application. Within the range of current intensities studied, the most optimal protocol for maximizing IL-1β release without inducing cell death was identified at electric charges equal to or near 144 mC, applied over a total duration of approximately 25 s. Our findings lay the groundwork for future in vivo studies assessing different electric charge of galvanic current, with the aim of yielding clinically relevant outcomes.